Auditory cortex activation is modulated by emotion: a functional near-infrared spectroscopy (fNIRS) study - Plichta, Michael M.; Gerdes, Antje B. M.; Alpers, Georg W.; Harnisch, W.; Brill, S.; Wieser, M. J.; Fallgatter, Andreas J. (NeuroImage, 2011)
Visual emotional stimuli evoke enhanced activation in early visual cortex areas which may help organisms to quickly detect biologically salient cues and initiate appropriate approach or avoidance behavior. Functional neuroimaging evidence for the modulation of other sensory modalities by emotion is scarce. Therefore, the aim of the present study was to test whether sensory facilitation by emotional cues can also be found in the auditory domain. We recorded auditory brain activation with functional near-infrared-spectroscopy (fNIRS), a non-invasive and silent neuroimaging technique, while participants were listening to standardized pleasant, unpleasant, and neutral sounds selected from the International Affective Digitized Sound System (IADS). Pleasant and unpleasant sounds led to increased auditory cortex activation as compared to neutral sounds. This is the first study to suggest that the enhanced activation of sensory areas in response to complex emotional stimuli is apparently not restricted to the visual domain but is also evident in the auditory domain.
Gesehen am 22.12.2022